Social media in business records / Suriani Jack … [et.al.] - Let, Elvina; Siman, Fatin Atirah; Diam, Jezreel Meggiddo; Wan Za’aba, Sharifah Ramiezah; Gerunsin, Wellace Bayang (Perpustakaan Tun Abdul Razak , Universiti Teknologi MARA Sarawak, 2022)
This chapters in book is mainly focusing on how business records management functions and the applications of social media in organizations. All articles that are included in this e-publication are taken from research papers that have been done from 2011 to 2022. All of these articles are in the scope of “Social Media Engagement: is it a Need or a Want in Business Records Management”.